Simultaneous saccharification and fermentation of steam exploded duckweed: Improvement of the ethanol yield by increasing yeast titre. (October 2015) - Zhao, X.; Moates, G.K.; Elliston, A.; Wilson, D.R.; Coleman, M.J.; Waldron, K.W.
Highlights: Steam explosion of duckweed enhances SSF at low (2% w/v) substrate concentrations. High substrate concentrations (20% w/v) result in much lower ethanol yields. Ethanol yields can be considerably increased with higher yeast inoculum. Or by preconditioning yeasts in steam explosion liquor containing inhibitors. The extra/preconditioned yeast metabolise fermentation inhibitors. Abstract: This study investigated the conversion of Lemna minor biomass to bioethanol. The biomass was pre-treated by steam explosion (SE, 210 °C, 10 min) and then subjected to simultaneous saccharification and fermentation (SSF) using Cellic® CTec 2 (20 U or 0.87 FPU g −1 substrate) cellulase plus β-glucosidase (2 U g −1 substrate) and a yeast inoculum of 10% (v/v or 8.0 × 10 7 cells mL −1 ). At a substrate concentration of 1% (w/v) an ethanol yield of 80% (w/w, theoretical) was achieved. However at a substrate concentration of 20% (w/v), the ethanol yield was lowered to 18.8% (w/w, theoretical). Yields were considerably improved by increasing the yeast titre in the inoculum or preconditioning the yeast on steam exploded liquor. These approaches enhanced the ethanol yield up to 70% (w/w, theoretical) at a substrate concentration of 20% (w/v) by metabolising fermentation inhibitors.